2014
DOI: 10.1136/bcr-2013-200392
|View full text |Cite
|
Sign up to set email alerts
|

Eating seeds from the ‘be still’ tree, yet having lucky nut poisoning: a case of acute yellow oleander poisoning

Abstract: SUMMARYA 25-year-old woman was evaluated and treated for ingestion of Thevetia peruviana seeds and flower petals -a natural digoxin cross reacting cardinolide-with intent to cause self-harm. The following case report provides the clinical presentation, treatment and management of acute yellow oleander poisoning. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Bradycardia and heart block are the most frequently reported cardiac abnormalities. [5,6] Fig 3 . showing seeds of yellow oleander in stomach…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bradycardia and heart block are the most frequently reported cardiac abnormalities. [5,6] Fig 3 . showing seeds of yellow oleander in stomach…”
Section: Discussionmentioning
confidence: 99%
“…In one study it was found to be the most common cause of acute poisoning in India. [5] Y. oleander toxicity is attributed to cardiac glycosides, including peruvoside, ruvoside, thevetin a, nerifolin and thevetin b. [8] Yellow oleander an ornamental shrub that usually grow up to 2 to 6 meters, leaves yielding a milky sap, and All parts of yellow oleander are toxic but roots and seeds are more toxic compared to other parts.…”
Section: Introductionmentioning
confidence: 99%
“…Ingestion of yellow oleander can lead to poisoning. The pharmacokinetics of this poisoning vary based on the concentration of cardiac glycosides in the ingested plant part and the time elapsed since ingestion [ 3 ]. The toxicity severity depends on multiple factors, including the form of ingested seeds (e.g., crushed seeds are more toxic), the extent of gastrointestinal absorption, post-ingestion vomiting, and the individual's overall health and existing comorbidities [ 4 ].…”
Section: Introductionmentioning
confidence: 99%